Learning Interest of Poliwangi Students to Learn Mathematics Engineering Through MOOCs Using Dummy Regression - Yuniwati, Ika; Yustita, Aprilia Divi; Hardiyanti, Siska Aprilia; Suardinata, I Wayan (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
MOOC is a learning system in the form of an online course that was massive and open to allow participants to enjoy unlimited and can be accessed via the web. Mathematics Techniques taught by using MOOC that will be developed are expected to be liked by students. Therefore it is necessary to do research related to student interest in studying the MOOC. This study uses a dummy regression model. Dummy regression is considered a suitable model because dummy regression can quantify qualitative data. Qualitative data here are obtained from questionnaires which distributed to 240 students. The questionnaire contains indicators of student interest in MOOC, including cognitive, affective, and psychomotor interests. The results of this study are the interest of students who do not want to study engineering mathematics through MOOC is lower than the interest of students who are interested in learning engineering mathematics through MOOC. Moreover, the interest of students who do not want to study engineering mathematics through MOOC is lower than the interest of students who do not like to study engineering mathematics through MOOC.